Apel do wspólnoty polskiej na świecie [ulotka] . Appeal to Polish community in the world. Flier - NSZZ "Solidarność". (NSZZ "Solidarność", 1989)
Red and black print on white paper. The flier contains an appeal of Lech Wałęsa to Polish emigre community for support to Solidarity in the June 1989 elections, followed by voting instructions, with Solidarity logotype printed in transverse.